ANALISIS STRUKTUR GEOLOGI BERDASARKAN DATA PERMUKAAN DAERAH BANJARHARJO, KABUPATEN BREBES, PROVINSI JAWA TENGAH: GEOLOGICAL STRUCTURE ANALYSIS BASED ON SURFACE DATA OF THE BANJARHARJO REGION, BREBES DISTRICT, CENTRAL JAVA PROVINCE - Maulana, Ilham; Triany, Novi (Universitas Trisakti, 2024)
The research area is administratively located in Banjarharjo Village, Banjarharjo District, Brebes Regency, Central Java Province. Geographically, the research area is located at coordinates 108o 49 '15.4